2013
DOI: 10.3126/ajn.v3i0.8982
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the sensitivity of CERES-Rice model: An experience of Nepal

Abstract: The experiment was conducted with four levels of nitrogen (40, 80,120 and 160 kg/ha) and 3 different cultivars (Prithivi hybrid), Masuli (HYV) and Sunaulo Sugandha (Aromatic).RMSE value (747.35 kg/ha, 1.106 days, 2.58 days and 0.004 kg/ha) and D-stat value (0.793, 0.99, 0.99 and 0.633) for grain yield, anthesis days, maturity days, and individual grain weight respectively. The objective of this study was to identify whether CSM-CERES-Rice model can be used in Nepalese condition and to evaluate the sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…2.8 tonha -1 , 2.5 tonha -1 , and 1.7 tonha -1 for rice, maize, wheat, respectively, very low as compared with other areas worldwide, e.g. 13,55). However, the finding that more erratically changing temperature (heat waves) and rainfall (wet/dry spells) cascades into more variable (insecure) food production is consistent with the findings reported above.…”
Section: Projected Impacts Of Climate Change In Nepalsupporting
confidence: 82%
“…2.8 tonha -1 , 2.5 tonha -1 , and 1.7 tonha -1 for rice, maize, wheat, respectively, very low as compared with other areas worldwide, e.g. 13,55). However, the finding that more erratically changing temperature (heat waves) and rainfall (wet/dry spells) cascades into more variable (insecure) food production is consistent with the findings reported above.…”
Section: Projected Impacts Of Climate Change In Nepalsupporting
confidence: 82%
“…Increase in temperature by the year 2020, 2050 and 2080 A.D. decreases the simulated grain yield to 4518, 4098, 2543 kg/ha, respectively and increase in CO 2 concentration and solar radiation can increase the yield slightly with increase in the minimum and maximum temperatures. Lamsal et al (2013) also reported the similar findings. The rate of senescence was increased due to the warm temperature which finally reduced the grain yield of rice (Hatfield & Pruegar, 2015).…”
Section: Climate Change Scenariossupporting
confidence: 69%
“…Sensitivity analyses are used to evaluate the responses of model outputs to changes in model input parameters and to quantify the relative importance of those responses [35,36]. Many studies have been conducted to evaluate the sensitivity of plant parameters and the management practices of different crops under different models [24,[37][38][39][40][41][42][43]. Although the sensitivity assessment of soil is essential [25], limited attention has been paid to evaluating the sensitivity of soil parameters [42].…”
Section: Introductionmentioning
confidence: 99%